The role of digital technology in people-centered development: the basic needs approach in the Kampung Marketer Program - Sulasih Sulasih; Agus Suroso; Weni Novandari; Suliyanto Suliyanto (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2022)
The Kampung Marketer program is a youth empowerment program specializing in digital marketing. The basic needs approach is used to evaluate community development. This approach states that it is necessary to have greater job opportunities, increase economic growth, and guarantee the community's basic needs for a better quality of life. This research aims to determine how digital roles are implemented in people-centered development and measure its impact with the basic needs approach. A qualitative approach uses a triangulation model that combines in-depth interviews, observations, and documents from Kampung Marketers. From the research results, it was found that digital resources aided people-centered development by increasing employment opportunities. In the 18 existing branches, the Kampung Marketer Program has accumulated 700 customer service and advertising skills. As a result of the program, the economic growth of communities with Kampung Marketer programs had increased, as indicated by the amount of income received by the empowered community of around IDR 1,000,000 to IDR 3,000,000 and the total income that was distributed being 1.3 billion. It impacts meeting the basic needs of society and increasing the younger generation's enthusiasm for continuing their studies. The members of Kampung Marketer also could now pay for their children's tuition and even bought houses and land. The older generation who did not have technological skills were also supported and empowered by the program by establishing a business called "Saung Makaryo." They were trained to produce goods in their respective homes, and Kampung Marketers marketed them.